Multisite Implementation of a Digital Wound Model of Care: A Post‐Implementation Multimethods Evaluation of Patient and Clinician Perspectives and Lessons Learned - Michelle Barakat‐Johnson; Clementine Mak; Michelle Lai; Phillip Baharudin; Darren Dela Rosa; Katja Heuer; Natalie Ko; Thomas Leong; Vivien Low‐Clarke; Apryl Repole‐Li Vaccari; Melissa T. Baysari (International Wound Journal, 2026)
ABSTRACT This study evaluated district‐wide implementation of a digital wound model of care combining an artificial intelligence–enabled application with a virtual command centre across four hospitals and five community health centres in Australia. A post‐implementation multimethods evaluation (January 2024–January 2026) of patients ( n = 94), frontline clinicians ( n = 75), and senior wound nurses ( n = 9) and a product manager ( n = 1) using surveys, semi‐structured interviews and analysis of governance meeting minutes. Patient satisfaction was high: 91% rated care as ‘excellent’ or ‘good’, 93% 'agreed' or 'strongly agreed' it was effective and 96% 'agreed' or 'strongly agreed' that they felt confident in the care they received from their wound care provider. Just over half (59%) felt they were meaningfully involved in decisions about their own care, an area identified for targeted improvement in future iterations of the model. The most cited virtual care benefits included improved condition understanding (63%), and reduced travel (49%). Among the 28 patient app users, 89% reported improved communication between them and the wound care provider and 79% self‐management confidence. Senior wound nurses rated the app highly for ease of use and continuity of care (both 86%), but poor connectivity was a limitation. Frontline clinicians valued enhanced documentation consistency but reported barriers including time pressures and training burden. This multisite implementation demonstrates that digital wound care models are highly acceptable and deliver perceived clinical benefit, while identifying patient involvement in decision‐making and clinician workflow integration as priority areas for future investment.